Sinonasal cancer encroaching the orbit: Ablation or preservation?. (March 2021) - Ferrari, Marco; Migliorati, Sara; Tomasoni, Michele; Crisafulli, Valentina; Nocivelli, Giorgio; Paderno, Alberto; Rampinelli, Vittorio; Taboni, Stefano; Schreiber, Alberto; Mattavelli, Davide; Lancini, Davide; Gualtieri, Tommaso; et al.
Highlights: Orbit encroachment by sinonasal cancer is assessed through analysis of 123 patients. MRI accuracy changes through orbital layers and according to pathological factors. Orbit-sparing surgery is oncologically sound in adequately selected patients. Non-surgical treatments should be preferred over upfront orbital ablation. Abstract: Background: Encroachment on the orbital cavity represents a challenge in the management of sinonasal cancer. Criteria guiding orbital preservation lack univocal consensus. Stage of orbital involvement is best assessed through magnetic resonance imaging (MRI). Methods: Patients affected by orbit-encroaching sinonasal cancer with available preoperative MRI, receiving surgery-based treatment at the University of Brescia between May 2005 and October 2018 were included. All cases were reviewed by expert radiologists and pathologists. Diagnostic performance of MRI was calculated using pathological information as reference. Survival analysis was performed. Results: The study included 123 patients. The orbit was abutted in 53 (43.1%) patients, whereas orbital invasion reached the periorbit in 18 (14.6%), extraconal fat and/or medial lacrimal sac in 29 (23.6%), extrinsic ocular muscles in 7 (5.7%), intraconal compartment in 4 (3.3%), and orbital apex in 12 (9.8%). Seventy-six (61.8%) patients received orbit-sparing surgery, 47 (38.2%) underwent orbital ablation (OA). Accuracy of MRI in detecting involvement by cancer was ≥80.0% for the orbital wall, extraconal fat, and muscles, and <80.0% for the periorbit and intraconal compartment. Previous surgery, neoadjuvant chemotherapy, and perineural invasion decreased MRI accuracy. Age, histology, tumor grade, pT category, N status, perineural invasion, orbital invasion stage, and need for OA were found to affect prognosis. Five-year orbital dysfunction-free survival was 92.8%. Conclusion: Conservative management of sinonasal cancers encroaching the orbit is feasible. MRI is essential to preoperatively stage orbital invasion, yet with some limitation. Given the dismal prognosis despite aggressive surgery, neoadjuvant non-surgical therapies should be considered in patients requiring OA.